Role of Preoperative Biomarkers in Predicting Myocardial Injury and Improving Postoperative Outcomes in Cardiac Surgery - Jaweria, Fatima; Sanaullah, Asjed (Indus Journal of Bioscience Research, 2025)
Background: Preoperative biomarkers serve as crucial indicators of myocardial injury risk in patients undergoing cardiac surgery. Identifying reliable biomarkers can enhance risk stratification, optimize surgical planning, and improve postoperative outcomes. This study evaluates the predictive role of preoperative biomarkers in myocardial injury and their influence on post-surgical recovery. Methodology: A retrospective case-control study was conducted at Mayo Hospital Lahore from February 03, 2023 to August 19, 2023, including 220 patients undergoing cardiac surgery. Patients were classified into cases (with myocardial injury) and controls (without myocardial injury) based on postoperative cardiac enzyme levels. Preoperative biomarkers assessed included Troponin I, CK-MB, NT-proBNP, CRP, and D-dimer. Intraoperative factors (bypass time, cross-clamp duration, blood loss, inotropic support) and postoperative outcomes (ICU stay, hospital stay, complications, mortality) were analyzed as secondary determinants. Statistical tests included independent t-tests and chi-square tests, with a significance threshold of p < 0.05. Results: Preoperative CK-MB levels were significantly higher in the myocardial injury group (15.92 ± 6.84 vs. 11.48 ± 5.23 ng/mL, p < 0.001), along with Troponin I (0.78 ± 0.34 vs. 0.42 ± 0.21 ng/mL, p < 0.001) and NT-proBNP (2651.42 ± 875.32 vs. 1987.64 ± 720.18 pg/mL, p = 0.002). CRP and D-dimer levels were also elevated in cases compared to controls (p = 0.008 and p = 0.014, respectively), confirming their role in predicting myocardial injury. While intraoperative factors were not independent predictors, longer bypass time (p = 0.027), cross-clamp duration (p = 0.015), and inotropic support requirement (p = 0.012) were significantly associated with myocardial injury when adjusted for preoperative biomarker levels. Postoperatively, the myocardial injury group experienced a longer ICU stay (8.4 ± 3.7 vs. 6.1 ± 2.8 days, p = 0.011), extended hospital stay (17.9 ± 6.5 vs. 14.2 ± 5.3 days, p = 0.019), and higher mortality (14.5% vs. 5.2%, p = 0.004). Conclusion: Elevated preoperative levels of CK-MB, Troponin I, NT-proBNP, CRP, and D-dimer were significant predictors of myocardial injury following cardiac surgery. Secondary intraoperative and postoperative factors were influenced by preoperative biomarker levels, underscoring their vital role in risk stratification. Routine biomarker assessment should be integrated into preoperative screening protocols to enhance patient outcomes. Further prospective studies are recommended to validate these findings.